2022
DOI: 10.1111/aas.14129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient characteristics and long‐term mortality between transferred and non‐transferred COVID‐19 patients in Dutch intensive care units: A national cohort study

Abstract: Background: COVID-19 patients were often transferred to other intensive care units (ICUs) to prevent that ICUs would reach their maximum capacity. However, transferring ICU patients is not free of risk. We aim to compare the characteristics and outcomes of transferred versus non-transferred COVID-19 ICU patients in the Netherlands. Methods: We included adult COVID-19 patients admitted to Dutch ICUs between March 1, 2020 and July 1, 2021. We compared the patient characteristics and outcomes of non-transferred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…The separate analysis was necessary, as ICU patients were relatively more often transferred and at the same time showed a much higher mortality than non-ICU patients. The nding regarding mortality of transferred ICU patients is in line with the great majority of the previous studies on mortality in ICU patients performed in different countries at different periods of time [5,7,8,[11][12][13], suggesting the validity and comparability of our data. When focusing on the mortality of non-ICU patients, our results appear novel but compatible with the literature, as in a previous study [5] no higher mortality of transferred patients was observed, when pooling ICU and non-ICU patients after adjustment for several risk factors.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The separate analysis was necessary, as ICU patients were relatively more often transferred and at the same time showed a much higher mortality than non-ICU patients. The nding regarding mortality of transferred ICU patients is in line with the great majority of the previous studies on mortality in ICU patients performed in different countries at different periods of time [5,7,8,[11][12][13], suggesting the validity and comparability of our data. When focusing on the mortality of non-ICU patients, our results appear novel but compatible with the literature, as in a previous study [5] no higher mortality of transferred patients was observed, when pooling ICU and non-ICU patients after adjustment for several risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…COVID-19 exerted considerable stress on medical capacity (e.g., hospital beds and medical staff [3,4], requiring a sophisticated patient management that included optimal allocation to the available hospital capacity and capability [5]. In Germany, as in other countries, this led to a high number of inter-hospital transfers [5][6][7][8][9], particularly regarding intensive care treatment, raising the question whether the transfers had an impact on patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Dutch study, we compared the patient characteristics and long-term mortality of transferred and nontransferred COVID-19 patients in intensive care units. Transferred patients were more often mechanically ventilated but less severely ill than nontransferred patients [3]. The difference between this study and ours may be related to the type of transfer (clinical, capacity, repatriation) and the national crisis management policy of the 2 countries during COVID.…”
Section: Discussioncontrasting
confidence: 64%